Application of Modified Jasper Jumper Appliance in Early Treatment of Class III Malocclusion (Three Case Reports) - Hülya Kılıçoğlu; Gülsün Külekçi; Ceylan Alioğlu (Galenos Yayinevi, 2011)
It was considered that Modified Jasper Jumper appliance could be a good alternative treatment for patients who were not able to keep cooperation in early treatment of Class III malocclusions. The aim of this case report, is to introduce Modified Jasper Jumper appliance which don't require patient cooperation in the early treatment of Class III malocclusion and to demonstrate the clinical use of the appliance.